Analisis Kepentingan Jerman dalam Pengiriman Main Battle Tank Leopard ke Indonesia (2012-2017) - Ilhamna Putri, Valery (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2021)
This article is intended to analyze the reason behind the shipment of Main Battle Tank (MBT) Leopard by Germany to Indonesia from the year of 2012 until year 2017. Arms transfer is used with the purpose to increase wealth, power and to produce innovation in production of military power of a state. Arms transfer is an essential part from international security structure because it can influence a shift in local and regional power. This article argued that there are three power dimensions along with the intended influence in arms transfer pursued by supplier country. The intended power dimensions are bargaining power, structural power, and hegemonic power. At the end of the article, it is concluded that three power dimensions stated above complete and relate to each other to fulfill the supplier country's interest.